2019
DOI: 10.1002/wmh3.291
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mortality in Nigeria: A Literature Review

Abstract: One hundred forty‐five Nigerian women die in childbirth every day. This review was conducted to evaluate the influences on maternal mortality in Nigeria. It is an analysis and synthesis of the professional literature surrounding maternal mortality in Nigeria and a review of articles in CINAHL, Health Source, Medline in EBSCO, including PubMed, ProQuest Health and Medical Complete, 2000–2015, analyzed and sorted into themes. The etiology of maternal mortality can be categorized as medical, socio‐economic, cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Uneducated women may find it difficult to recognize danger signs, are less economically empowered to seek care, have poor health seeking behaviours, and are highly dependent on the approval of their husband or male head of household to access health care. They therefore do not attend antenatal care and present late to maternal healthcare facilities when complications have already supervened [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uneducated women may find it difficult to recognize danger signs, are less economically empowered to seek care, have poor health seeking behaviours, and are highly dependent on the approval of their husband or male head of household to access health care. They therefore do not attend antenatal care and present late to maternal healthcare facilities when complications have already supervened [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 6 Some family-level characteristics such as economic status and marital relationships, social–cultural factors such as religion, gender norms and health belief have also been identified as key determinants. 12 13 While this showed that causes of maternal mortality are multifaceted, most interventions designed to tackle this major public health problem relate to the medical causes.…”
Section: Introductionmentioning
confidence: 99%
“…Predictably, maternal mortality in Nigeria remains unacceptably high at a ratio of 917 deaths per 100,000 live births and 60,000 maternal deaths occurring annually, most of which are preventable (WHO, 2019). This indisputably makes maternal mortality a human rights issue in Nigeria (Olonade, Olawande, Alabi, & Imhonopi 2019;Piane, 2019). The preamble of the 1946 Constitution of the WHO states that "the enjoyment of the highest attainable standard of health is one of the fundamental rights of every human being…."…”
Section: Introductionmentioning
confidence: 99%